Historical Memory of the First World War: Notes on its Shaping in Russia and in the West - E. S. Senjavskaja (Vestnik MGIMO-Universiteta)
The article deals with the reasons, why the First World War didn’t leave stable heroic symbols in the historical memory of the Russians and occupied only marginal place. The influence of ideological and political background on the interpretation of the past, the role of the power elite in shaping the aims of the retrospective propaganda. The picture of the military events of 1914 – 1918 in Russian and foreign fiction literature has been given on the comparative basis.